GDP-Mannose Pyrophosphorylase: A Biologically Validated Target for Drug Development Against Leishmaniasis - Pomel, Sébastien; Mao, Wei; Ha-Duong, Tâp; Cavé, Christian; Loiseau, Philippe M. (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmaniases are neglected tropical diseases that threaten about 350 million people in 98 countries around the world. In order to find new antileishmanial drugs, an original approach consists in reducing the pathogenic effect of the parasite by impairing the glycoconjugate biosynthesis, necessary for parasite recognition and internalization by the macrophage. Some proteins appear to be critical in this way, and one of them, the GDP-Mannose Pyrophosphorylase (GDP-MP), is an attractive target for the design of specific inhibitors as it is essential for Leishmania survival and it presents significant differences with the host counterpart. Two GDP-MP inhibitors, compounds A and B, have been identified in two distinct studies by high throughput screening and by a rational approach based on molecular modeling, respectively. Compound B was found to be the most promising as it exhibited specific competitive inhibition of leishmanial GDP-MP and antileishmanial activities at the micromolar range with interesting selectivity indexes, as opposed to compound A. Therefore, compound B can be used as a pharmacological tool for the development of new specific antileishmanial drugs.